Psychosocial fuctors associated with conswnption of alcoholic beverages and tobacco in late adolescents from a privare university in Lima - Chau, Cecilia (1995)
This paper main objectives are to evaluate the characteristics of tobacco and alcoholic beverage consumption as well as associated psychosocial factors in 466 adolescent freshmen in a private university in Lima.We found life prevalence and current consumption rates are higher for alcohol among male students, being beer the most consumed alcohol beverage than other spirits. The pattern of consumption of these substances is social and recreational. With regard to psychosocial aspects, similarities were found between alcoholic beverages and tobacco consumers and nonconsumers or totally abstemious ones (neither alcohol nor tobacco).Only nine adolescents, out of 466, reported that they had never consumed alcoholic beverages nor tobacco (non-consumers) and eight percent of the sample reported illegal psychoactive substance live prevalence.